A neural marker of rapid discrimination of facial expression in 3.5- and 7-month-old infants - Poncet, Fanny; Leleu, Arnaud; Rekow, Diane; Damon, Fabrice; Dzhelyova, Milena P.; Schaal, Benoist; Durand, Karine; Faivre, Laurence; Rossion, Bruno; Baudouin, Jean-Yves (Frontiers in Neuroscience, 2022)
Infants’ ability to discriminate facial expressions has been widely explored, but little is known about the rapid and automatic ability to discriminate a given expression against many others in a single experiment. Here we investigated the development of facial expression discrimination in infancy with fast periodic visual stimulation coupled with scalp electroencephalography (EEG). EEG was recorded in eighteen 3.5- and eighteen 7-month-old infants presented with a female face expressing disgust, happiness, or a neutral emotion (in different stimulation sequences) at a base stimulation frequency of 6 Hz. Pictures of the same individual expressing other emotions (either anger, disgust, fear, happiness, sadness, or neutrality, randomly and excluding the expression presented at the base frequency) were introduced every 6 stimuli (at 1 Hz). Frequency-domain analysis revealed an objective (i.e., at the predefined 1-Hz frequency and harmonics) expression-change brain response in both 3.5- and 7-month-olds, indicating the visual discrimination of various expressions from disgust, happiness and neutrality from these early ages. At 3.5 months, the responses to the discrimination from disgust and happiness expressions were located mainly on medial occipital sites, whereas a more lateral topography was found for the response to the discrimination from neutrality, suggesting that expression discrimination from an emotionally neutral face relies on distinct visual cues than discrimination from a disgust or happy face. Finally, expression discrimination from happiness was associated with a reduced activity over posterior areas and an additional response over central frontal scalp regions at 7 months as compared to 3.5 months. This result suggests developmental changes in the processing of happiness expressions as compared to negative/neutral ones within this age range.